Sleep-related rhythmic movement disorder in children: a mini-review - Lam, Nhi; Veeravigrom, Montida (Frontiers in Neurology, 2023)
Sleep-related rhythmic movement disorder (SRRMD) is rare in children, with some patients experiencing persistent SRRMD during adolescence and adulthood. Rhythmic movement during sleep in children is often asymptomatic and considered a benign condition. It is classified as SRRMD when movement significantly disrupts sleep, results in daytime functional impairment, or causes self-inflicted body injury. Several studies have demonstrated that SRRMD occurs in all sleep stages. Few studies have investigated rhythmic movement disorder (RMD) in children. SRRMD is a clinical diagnosis supported by home video recordings. When the clinical history is insufficient to provide a definitive diagnosis of SRRMD, and other sleep-related conditions or seizure disorders are suspected, video-polysomnography is indicated. There are currently no clinical guidelines for treating SRRMD.